What is urban sprawl in Flanders? - Vermeiren, Karolien; Poelmans, Lien; Engelen, Guy; Loris, Isabelle; Pisman, Ann (My University, 2018)
At the country level, Belgium was found to be the European country with the highest degree of urban sprawl (EEA report on Urban sprawl in Europe, 2016). Given this urban fragmentation of the landscape, concerns and discussions rise about the pros and cons of this development and strategies to mitigate or stop urban sprawl. Urban sprawl can refer to both a state (level of sprawl at a certain point in time) and a process (evolution of the level of sprawl in time). To gain better insights in the state of urban sprawl, detailed data of high quality are necessary. Several measures have been used in the literature to quantify (different aspects of) urban sprawl. Depending on the measure, but also on the type of input data used, different results can be obtained which in turn can lead to completely different interpretations and conclusions regarding the level of urban sprawl in Flanders. In this paper we analyse the effect of alternative input data on the outcome of the quantitative sprawl measure WUP (weighted urban proliferation) (EEA, 2016). Using sealed surfaces as an input to calculate WUP leads overall to an underestimation of the space taken in by urban settlements, hence of the importance of urban sprawl. Using the total settlement area of Flanders (including sealed surfaces, but also gardens, parks, etc.) leads to a much better representation of the phenomenon of urban sprawl. The process of urban sprawl in Flanders is analysed by means of a temporal analysis using Landsat images of 1976, 1988 and 2000. The images are processed into urban settlement maps and urban sprawl is measured by means of WUP for the different time steps. Difference maps show the temporal and spatial dynamics of urban sprawl throughout the region. Finally, in order to make measures of urban sprawl, and hence the phenomenon itself, easier to interpret and understand for a wider public, and, to answer the question What is urban sprawl and where is it affecting Flanders? , the WUP-maps are translated into an urban sprawl typology map with characterizing examples and typical spatial configurations for each type. These will be used to stimulate the public awareness and debate with respect to sprawl and the generally devastating effects that it has on the Flemish landscapes.
Keywords: Zersiedelung; Verstädterung; Quantifizierung; Raumanalyse; Analysemethode; Regionalentwicklung